2019
DOI: 10.1007/s13538-019-00669-2
|View full text |Cite
|
Sign up to set email alerts
|

Single-Capture Cross Sections from Biological Molecules and Noble Gases by Bare Ion Impact

Abstract: In this work, we report theoretical electron capture cross sections for single-electron removal from molecules of biological interest and noble gases by bare ion (H + and H e 2+) impact at energies ranging from 25 to 10,000 keV/amu. We use a distorted wave (DW) method where the intermediate continuum state of the active electron with the target ion has been taken into account. This method is developed within the framework of the independent electron model taking particular care of the representation of the bou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 69 publications
0
3
1
Order By: Relevance
“…a similar impact energy dependence, at least down to E = 50 keV where the CDW-EIS calculation terminates. The cross-section curve from[20] extends further down to E = 25 keV and indicates an even stronger increase toward low energies than the present CNDO calculation, which significantly overestimates the measurements in this region. We note thatPurkait et al also reported IAM-AR calculations in their work which for p-CH 4 collisions are in close agreement with their CNDO results.…”
contrasting
confidence: 64%
See 3 more Smart Citations
“…a similar impact energy dependence, at least down to E = 50 keV where the CDW-EIS calculation terminates. The cross-section curve from[20] extends further down to E = 25 keV and indicates an even stronger increase toward low energies than the present CNDO calculation, which significantly overestimates the measurements in this region. We note thatPurkait et al also reported IAM-AR calculations in their work which for p-CH 4 collisions are in close agreement with their CNDO results.…”
contrasting
confidence: 64%
“…The details of the calculations show that at low impact energies the resonant capture from H(1s) dominates, while capture from the carbon AOs gains relative importance toward higher energies. The differences in the orbital-specific cross sections and those between the gross populations and occupation numbers listed in IAM-PCM, IAM-AR, and CNDO: present calculations, CDW-EIS-CNDO [7], DW-CNDO [20]; experiments: Rudd83 [21], Toburen68 [22], Sanders03: [23].…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations